Recent Developments in Understanding Spirituality as Exemplified by the Concept of Self-Transcendence - Jastrzębski, Andrzej (Verbum Vitae, 2021)
The recent history of science has witnessed many shifts of paradigms. One of the major changes has been observed in the shift of spirituality, transforming from a traditional faith-based notion to a more secular or postmodern one. These changes are confusing for many modern people as they are not able to follow these rapid developments. This article is an attempt at providing a conceptual framework to understand the changes that the notion of spirituality has undergone using the concept of self-transcendence and its two major dimensions: vertical and horizontal. This model will serve to evaluate different ways of defining spirituality in both theology and the social sciences and to indicate the provenience of their roots in both disciplines. In conclusion, self-transcendence will be compared with the concept of self-actualization.